Tagging and Targeting of Energy Efficiency Subsidies - Allcott, Hunt; Knittel, Christopher; Taubinsky, Dmitry (American Economic Review, 2015)
A corrective tax or subsidy is “well-targeted” if it primarily affects choices that are more distorted by market failures. Energy efficiency subsidies are designed to correct multiple distortions: externalities, credit constraints, “landlord-tenant” information asymmetries, imperfect information, and inattention. We show that three important energy efficiency subsidies are primarily taken up by consumers who are wealthier, own their own homes, and are more informed about and attentive to energy costs. This suggests that these subsidies are poorly targeted at the market failures they were designed to address. However, we show that “tagging” can lead to large efficiency gains.